Antimicrobial Efficacy of Methanolic Extracts of Fagonia cretica - Thetwar, L.K.; Singh Thakur, Aradhana; Shrivastava, Seema; Augor, M.R.; Tandon, R.C.; Deshmukh, N.C. (Asian Journal of Chemistry, 2010)
The methanolic extract obtained from the flowers of Fagonia cretica (Family Zygophyllaceae), was tested for its antimicrobial activity against fungi: (i) Aspergllus niger (ii) Aspergillus funigatus for antifungal activity; and bacteria: (i) Escherichia coli, (ii) Proteus vulgaris (iii) Streptococcus agalacties and (iv) Bacillus anthracis for antibacterial activity.